ANALISIS KETERSEDIAAN LAHAN PANGAN BERKELANJUTAN DI KECAMATAN MAPANGET KOTA MANADO - Hizkia Bahihi; Zetly E. Tamod; Sandra E. Pakasi (COCOS, 2019)
ABSTRACT Food Agriculture Land is a limited amount of natural resources, the increasing need for land resources by humans has given its own pattern of land use patterns in an area. Research conducted in the study area is to identify potential land for sustainable food agriculture, using the field survey method with land unit approach and land characteristics for maize (Zea mays L.) and cassava (Manihot) namely rainfall and slope. The results showed the total area of Mapanget Subdistrict was 5414.6 hectares, based on the results of the analysis showed the potential land for corn crops suitable (S1) 3886.75 hectares with a percentage of 71.76 of the total land area in Mapanget District, Land Quite Appropriate (S2) 470.56 hectares with a percentage of 8.75 of the area of land in Mapanget District, marginal land (S3) of 35.59 hectares with a percentage of 0.62 of Mapanget District area. Cassava Plants with marginal suitable land (S3) 4392.9 hectares with a percentage of 81.13 of the area of land in Mapanget District. Keywords: Availability of Sustainable Food Land, Land Area